Characterization of Cu2SnS3 polymorphism and its impact on optoelectronic properties. Issue 45 (9th November 2017) - Oliva, Florian; Arqués, Laia; Acebo, Laura; Guc, Maxim; Sánchez, Yudania; Alcobé, Xavier; Pérez-Rodríguez, Alejandro; Saucedo, Edgardo; Izquierdo-Roca, Victor
Abstract : Temperature induced Cu2 SnS3 phase transition from a defective cubic to a monoclinic structure assessed by Raman spectroscopy and leading to higher photovoltaic efficiency. Abstract : Earth abundant compounds are of interest as a possible alternative to more mature thin film based technologies. Cu2 SnZnSe4 (CZTS) is the most studied material but its development is impeded by an easy formation of secondary phases, decomposition effects during both synthesis and post process treatments, and formation of Cu–Zn defects resulting in limited device performance. In this context, Cu2 SnS3 (CTS) is an interesting substitute with suitable optoelectronic properties and a wider stable composition range with fewer constituents hence (avoiding Zn related defects). Currently the technology is still in an early stage of development with a 4.63% record efficiency (6% with an alloy with Ge) and faces serious issues related to the formation and coexistence of different polymorphic/stoichiometric phases indicating that precise composition control and phase identification are still needed. In this work, an analysis of CTS thin film absorbers is presented. A comparative study by X-ray diffraction profile refinement and Raman spectroscopy allowed the assessment of both cubic and monoclinic CTS phases formed at different annealing temperatures. In addition Raman analysis of precursors sulfurized at different temperatures revealed a blue shift as well as a reduction of the Full Width at Half Maximum (FWHM) of the two dominant peaks for temperatures close to 550 °C, which is interpreted as a CTS phase transition in the absorber layer. This alteration was also correlated with the optoelectronic properties of devices. A higher V oc and J sc are obtained for samples with 30% monoclinic CTS phase concentration which led to a record efficiency of 2.4%. It is then assumed that higher efficiencies could be achieved for a pure monoclinic CTS layer. In this sense, a non-destructive methodology for the fast evaluation of cubic Cu2 SnS3 formation at the surface is proposed.